Restriction by SAMHD1 limits cGAS/STING-dependent innate and adaptive immune responses to HIV-1 - Maelfait, J; Bridgeman, A; Benlahrech, A; Cursi, C; Rehwinkel, J (Cell Press, 2016)
SAMHD1 is a restriction factor for HIV-1 infection. . SAMHD1 mutations cause the autoinflammatory Aicardi-Goutières syndrome that is characterized by chronic type I interferon (IFN) secretion. We show that the spontaneous IFN response in SAMHD1-deficient cells and mice requires the cGAS/STING cytosolic DNA-sensing pathway. We provide genetic evidence that cell-autonomous control of lentivirus infection in myeloid cells by SAMHD1 limits virus-induced production of IFNs and the induction of co-stimulatory markers. This program of myeloid cell activation required reverse transcription, cGAS and STING, and signaling through the IFN receptor. Furthermore, SAMHD1 reduced the induction of virus-specific cytotoxic T cells in vivo. Therefore, virus restriction by SAMHD1 limits the magnitude of IFN and T cell responses. This demonstrates a competition between cell-autonomous virus control and subsequent innate and adaptive immune responses, a concept with important implications for the treatment of infection. Restriction factors defend infected cells against viruses. Maelfait et al. find that SAMHD1, which blocks HIV-1 infection in myeloid cells, prevents innate sensing of infection via cGAS/STING. Furthermore, SAMHD1 curtails virus-specific T cell responses in vivo. Restriction by SAMHD1, therefore, limits subsequent innate and adaptive immune responses.